Dose Physiologically Performing Vigorous Exercises Good for Body Over Time - Habibzadeh, Nasim (International Physiology Journal, 2018)
A commentary addresses the benefits and risks of vigorous exercise over time from a physiological perspective, discussing adaptation, monitoring, and individualized recommendations.
Keywords: Vigorous Exercise; Physiological; Risks; Adaptation; Monitoring